The Intersection of Cultural Characteristics and Genetics on the Prevalence of Delayed Sleep Phase Syndrome in Brazilian and Japanese Adults - Abram Estafanous; Karim Sedky (Journal of Sleep And Sleep Disorder Research, 2020)
Delayed sleep phase syndrome (DSPS) is a circadian rhythm disorder where individuals experience difficulty modifying the time they go to sleep and wake up in response to environmental changes. The circadian rhythm itself is regulated by a variety of clock genes, and various other genes (e.g., AA-NAT gene, CKIϵ gene) code for proteins that regulate clock genes. Various polymorphisms of the clock gene influencers have been shown to increase susceptibility to DSPS. This paper seeks to examine how certain cultural characteristics (e.g., napping, timing of meals, exposure to artificial light) and the presence of the AA-NAT gene (G619A polymorphism) and the CKIϵ gene (S408N polymorphism) influence the prevalence of DSPS amongst Japanese and Brazilian populations.
Keywords: Sleep